Remarks and advice to the study of early arthropod succession near melting glaciers - Sigmund Hågvar; Barbara Valle; Mauro Gobbi (Arctic, Antarctic, and Alpine Research)
Melting glaciers give a unique possibility to study how life colonizes newly exposed ground. Research during the last two decades has shown that arthropods play a key role in establishing the first functioning ecosystems. However, there are still gaps in our knowledge about this succession process and a need to identify key research directions. Good case studies are the basis for a general understanding of patterns and driving forces in primary succession. We present remarks and advice on this topic, using examples from European studies. We explore the driving forces supporting the early ecosystem, discuss the ability of certain micro- and macroarthropods to be pioneers, and highlight the autecology of pioneer species and their role in building early trophic networks. Relevant research questions are identified. Different colonization patterns are discussed, and we stress the importance of a geoecological approach to the succession. We discuss relevant methods to collect sufficient material, how to tackle the scale problem and “ecological noise,” and the importance of a good taxonomic resolution. The present “package” of updated knowledge, research questions, and advice about fieldwork practice is meant especially for ecologists who are in their early phase of investigating succession in glacier forelands.